Engineering–geological conditions of the Dnipro slopes in the central area of Kyiv: a research retrospective and analysis of landslide hazard factors - KRIL, Tetiana; STRELTSOV, Anton (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. This article presents the results of an analysis of the engineering-geological conditions of the Dnipro slopes within the central historical area of Kyiv. The main objective of the study is to identify natural and anthropogenic factors influencing the development of landslide processes, as well as to form a contemporary understanding of the conditions necessary to ensure the stability of the natural system in the study area. Methods. To determine the dynamics of landslide development on the Dnipro slopes of Kyiv, a retrospective analysis of landslide-prone areas was conducted. This included photographic documentation of the current slope conditions and comparison with images from archival sources. The analysis of engineering-geological conditions and the factors driving landslide displacements was carried out using analytical, statistical, and cartographic methods. Geographic Information Systems (GIS), including ArcGIS and Surfer software, were used to construct cartographic models. Engineering-geological cross-sections were developed using AutoCAD tools. Results. The periods of scientific research on landslide hazards of the Dnipro slopes and efforts to stabilize them have been systematized, identifying five key research stages, including those conducted in the modern era since Ukraine's independence. Based on the understanding of the factors contributing to landslide development within the study area, three zones were identified and their engineering-geological characteristics were described. Areas with the highest landslide hazard were determined by slope angles ranging from 15 to 25°, occupying between 25 % and 34 % of the surface area depending on the specific slope section (Old Kyiv, Central, Zalavrskyi). It was established that the most significant factors contributing to the reduction of slope system stability are: soil water saturation (due to atmospheric precipitation and leakage from water supply networks), additional loading of slopes during urban development, engineering interventions without consideration of engineering-geological specifics, and dynamic loads (from transportation and construction activities). The cumulative impact of these factors was analyzed, and the consequences of their interaction were systematized, showing that they collectively lead to the destabilization of the slope system. Сonclusions. Based on the results, directions for the conceptual foundations of a systematic approach to ensuring the stability of the Dnipro slopes have been formulated. This approach involves the coordinated application of engineering-geological monitoring, the updating of engineering-geological zoning of the Dnipro slope, and the risk-based ranking of landslide hazards. It also includes the development of principles for rational urban planning on slopes and the optimization of anti-landslide measures, with mandatory consideration of the historical and cultural value of the study area.
Keywords: engineering-geological conditions; Dnipro slopes; landslides; landslide hazard factors; historical areas